Tax avoidance and tax reduction within the framework of the South African income tax legislation, with special reference to the effect on the fiscus and to current anomalies and inequities - Silke, Aubrey S (College of Accounting, 2015)
The subject of tax avoidance and tax reduction within the framework of the income tax legislation has so far not been dealt with in any work in South Africa and this is, therefore, the first work of its kind. My approach in this work has generally been, firstly, to set out the effect of the law in the light of the court decisions, the depart- mental practice and my own interpretations; secondly, to consider and discuss the extent to which taxpayers can arrange their affairs within the letter of the law in order to avoid or reduce tax and the prejudicial effect on the public revenue, and finally to offer my criticisms, suggestions and recommendations. It was inevitable that during the course of my studies and investigation into the workings of the Income Tax Act and the incidence of the taxes levied, various anomalies, inequities and obscurities would present themselves. Although some of these bear no or little relation to the problem of tax avoidance and tax reduction, I have nevertheless considered it necessary to deal with them in this work. Often they lead to results quite opposed to well-established commercial and accountancy practice. I have attempted to show how this conflict that exists between the Income Tax Act and the accountant's and business man's approach frequently results in the taxable income not coinciding with the profits as ascertained on the basis of ordinary, commercial and accountancy principles. Many of these aspects have up till now received very scant thought, and I have, therefore, felt that they should be clarified with a view to making both the taxpaying public and the fiscus fully conscious of them. The legislator and the taxpayer should be ever mindful of anomalies, inequities and obscurities in the law, because only by continual discussion and criticism can one hope for their ultimate eradication and hence for a better and fairer tax system.